Plant Diversity On Protected Forest Vegetation Of Dempo Mountains, Pagar Alam, South Sumatera - Anita Restu Puji Raharjeng; Deby Noviyanti; Eli Apriana; Laila Fahriati; Yunita Dwi Hastati (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2019)
Vegetation is a collection of plants that usually consist of several species and live together in one place. Vegetation analysis is a way of studying the composition (component type) and the shape (structure) of vegetation or vegetation communities. Forests are the most important habitat component of life, hence the condition of plant communities within the forest, whether plant species composition, species dominance, density or closure of the canopy should be measured. The island of Sumatra is one of the most diverse ecoregion regions in the world. World Wildlife Fund for Nature (WWF) as one of the world's conservation organizations incorporates mountainous rainforest as a conservation area. The Sumatra mountain forests are one of the 200 critically endorsed ecoregions and a priority of global conservation. Mount Dempo is a protected forest area located on a cluster of hills line the island of Sumatra. This mountain has a height of 3159 asl (above sea level) and is the highest mountain in the area of South Sumatra. This study aims to determine the diversity of plants in the protected forest vegetation of Mount Dempo, Pagar Alam City, South Sumatera. Vegetation analysis was done by purposive sampling with bitterlich method, i.e measurement done on plot measuring 2x2, 5x5, 10x10, and 20x20 m. Analyzes were performed on two plots of different locations, and all plant species found in each plot were recorded of the type and amount. The parameters measured include the type name, the individual number of each type, the diameter, the height, and the height of the free branch. The results obtained at the Importance Value Index (INP) in Gunung Dempo, Pagar Alam of 294 stated that Mount Dempo has a high vegetation that is still preserving the existing plant, but it is also able to used as tourist visit as the stage of environmental and nature care.